Chat GPT e Geografia: Novos Paradigmas para a ciência - Guilherme Almussa Leite Torres; Kevin Hyslop (Confins)
The set of commented images presented aims to demonstrate the answers Chat GPT Artificial Intelligence of would give to simple questions widely discussed in Geography studies and related areas